Tantangan Pembangunan Kependudukan Provinsi Nusa Tenggara Barat - Andi Pramaria; Gusti Bagus Kertayasa; Lalu Agustian Kusumaredi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The population development of West Nusa Tenggara Province has a high population growth rate, uneven population density, and low Human Development Index (HDI). Although the demographic bonus has been achieved, the windows of opportunity were still difficult to be achieved. The purpose of this study was to design a population development strategy based on the West Nusa Tenggara region. The method used was desk research, with restrospective data from the goverments’ 2020 Population Census and discussions with stakeholders. The results of the study showed that the population growth rate reached 1.63% while the National was 1.25%. The Dependency Ratio was 48.66, the population density of Lombok is 756.86 people/km2 and Sumbawa was 99.77 people/km2. HDI value was 68.25 with rank 29 among 34 provinces. The main challenges in population development in the future are population control, improvement of population’s capacity building, utilization of demographic bonuses, population distribution improvement, improving education, health and mobility of a productive population to increase HDI. The population development strategies is needed to achieve the desired conditions